2010
DOI: 10.1007/s11255-010-9798-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart failure on the incidence of contrast-induced nephropathy in patients with chronic kidney disease

Abstract: We randomized patients with chronic kidney disease (serum creatinine ≥ 1.5 mg/dl or glomerular filtration rate (GFR) <60 ml/min/1.73 m²) in a double-blind fashion to receive saline or sodium bicarbonate prior to and after cardiac or vascular angiography. The primary endpoint was contrast-induced nephropathy (CIN), defined as an increase in serum creatinine by 25% or by 0.5 mg/dl from baseline. Patients with congestive heart failure (CHF), cardiac ejection fraction (EF) <30%, or GFR < 20 ml/min/1.73 m² were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
(29 reference statements)
0
29
1
Order By: Relevance
“…Heart failure (i.e., LVEF \ 40%) is another potential indicator of hemodynamic instability, and it is an independent risk factor for CIN [27]; however, it was not observed in our study. To protect renal function, it may be beneficial to perform elective PCI of non-infarct-related arteries for patients with multi-vessel disease, especially in those whose eGFR is somewhat decreased.…”
Section: Discussioncontrasting
confidence: 87%
“…Heart failure (i.e., LVEF \ 40%) is another potential indicator of hemodynamic instability, and it is an independent risk factor for CIN [27]; however, it was not observed in our study. To protect renal function, it may be beneficial to perform elective PCI of non-infarct-related arteries for patients with multi-vessel disease, especially in those whose eGFR is somewhat decreased.…”
Section: Discussioncontrasting
confidence: 87%
“…As another well-known risk factor for CIN, CHF contributes to the development of CIN, 19) because the renin-angiotensin-aldosterone system (RAAS) increases the level of circulating vasoconstrictive neurohormones and elevates systemic vascular resistance in CHF patients, leading to systemic vasodilation and renal hypoperfusion. Many studies have proven that patients with severe CHF with New York Heart Association (NYHA) class 3-4 have a higher incidence of CIN.…”
Section: )mentioning
confidence: 99%
“…Recent studies focused on the comparative effectiveness of IV sodium bicarbonate (bicarbonate) and IV sodium chloride (saline) based on the hypothesis that alkalinization of tubular fluid with bicarbonate will decrease the generation of injurious reactive oxygen species. Several trials suggested bicarbonate to be more effective than saline (5)(6)(7)(8)(9)(10)(11)(12), whereas others reported no difference (13)(14)(15)(16)(17)(18)(19)(20)(21). A second preventive intervention that has received substantial attention is the administration of N-acetylcysteine (NAC), an antioxidant with vasodilatory properties.…”
Section: Introductionmentioning
confidence: 99%